2015
DOI: 10.1016/j.canep.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of C-peptide levels and colorectal adenoma incidence

Abstract: Our results suggest that higher C-peptide levels were not associated with colorectal adenoma incidence in this study population. Other biological pathways associated with obesity may be more relevant to the early stages of colorectal tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…A recent meta-analysis of 4 cohorts and 10 case-control studies found no associations between adenoma and 3 most studied circulating inflammation markers CRP, IL-6, and TNF-α [136]. Similarly, no significant associations were found for C-peptide, GM-CSF, interferon-α (IFN-α), IL-1β, IL-2, IL-4, IL-6, IL-7, IL-10, IL-12, IL-17A, MIP-1β, and vascular endothelial growth factor and adenoma [137][138][139]. Although associations were reported for IFN-α2, IL-7, IL-8, MCP-3, and SIL-4R in cross-sectional analyses [137,140] they have not been prospectively confirmed.…”
Section: Circulating Inflammation Markersmentioning
confidence: 98%
“…A recent meta-analysis of 4 cohorts and 10 case-control studies found no associations between adenoma and 3 most studied circulating inflammation markers CRP, IL-6, and TNF-α [136]. Similarly, no significant associations were found for C-peptide, GM-CSF, interferon-α (IFN-α), IL-1β, IL-2, IL-4, IL-6, IL-7, IL-10, IL-12, IL-17A, MIP-1β, and vascular endothelial growth factor and adenoma [137][138][139]. Although associations were reported for IFN-α2, IL-7, IL-8, MCP-3, and SIL-4R in cross-sectional analyses [137,140] they have not been prospectively confirmed.…”
Section: Circulating Inflammation Markersmentioning
confidence: 98%